Pengembangan dan Peningkatan Keterampilan Guru PAUD melalui Pelatihan Microsoft Word: Studi Kasus di PAUD Tunas Bangsa 05 - Saputri, Daniati Uki Eka; Firasari, Elly; Khasanah, Nurul; Cahyanti, F. Lia Dwi (Fakultas Teknik dan Ilmu Komputer, 2024)
The Microsoft Office training, specifically focusing on Microsoft Word, for the teaching staff of PAUD Tunas Bangsa 05 aimed to enhance technological skills to support educational quality. Conducted by a team of lecturers from Universitas Nusa Mandiri on May 18, 2024, the training was met with high enthusiasm from the participants. The methods employed included material presentation, hands-on practice, and Q&A sessions. Evaluation results indicated a significant improvement in participants' understanding and skills in using Microsoft Word. They were able to utilize the application to create more organized and professional documents, positively impacting the teaching-learning process. The activity successfully achieved its objectives and received positive feedback, also indicating the need for further training. Consequently, this training contributes to the professional development of the teaching staff and the enhancement of educational quality at PAUD Tunas Bangsa 05